(untitled) (Global Journal of Science Frontier Research, 2015)
Contract farming requires a long term commitment from both the contracted growers and sponsoring firms. Exploitative arrangements can jeopardize agribusiness investments. The study revealed that the contracted sugarcane growers reacted significantly towards immediate payment, arranging credit for infrastructure, implements and machineries on custom hiring, increasing risk bearing abilities, conflict resolution, quality production, transparency in measurement, contingent measures in catastrophes, exposure visit etc. The sponsoring firms have to analyze all these reactions of the respondents and extend all possible supports for sustainability of the contract farming in sugarcane cultivation.